Exploring the birth of modern art in Borneo, post-war era 1945 to 1970 - Rahah Haji Hasan,; Faridah Sahari, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper describes the development of modern art in Borneo particularly in Sarawak, Sabah and Brunei, after the Second World War until the 1970s. This was the period when British Colonial government dictated the education system, which consequentially inculcated visual art through art and craft subject imposed on all vernacular schools in Borneo. British influence within the state governance, social and education system designed with Western ideology, created not only westernized society and mind-set, but at the same time generated artistic opportunities for emerging local painters to be involved in the initiation of Modern Art in Borneo. Through historical method and analysis of primary and secondary data, it was obvious that the existence of colonial government departments and institutions such as museums and teaching colleges, and other social organization in Borneo at that time, contributed significantly to artistic movement? The similar structure and motivation of development in other areas of Borneo, confirmed that artistic affirmation of modern art advanced homogenously. Their understanding of easel painting as well as unique interpretation of culture once distanced from traditional art, resulting in a new visual image that transcended their ethnicity and identity through new medium and tools. These meticulous interventions modestly visualized in each painting as discussed in this paper, hopefully will give a deeper understanding and appreciation towards the history of modern art in Borneo.